ANALISIS PERAN PEMBIAYAAN USAHA MIKRO PADA USAHA MIKRO KECIL DAN MENENGAH DI BANK SYARIAH INDONESIA KANTOR CABANG PEMBANTU TAJUR, KOTA BOGOR, JAWA BARAT - Rahman, Elisa; Trihantana, Rully; Suryani, Ermi (SAHID BANKING JOURNAL, 2024)
Bank Syariah Indonesia KCP Bogor Tajur 1 is one of the financial institutions that distributes People's Business Credit funds to MSMEs. This study aims to find out how the role of Bank Syariah Indonesia KCP Bogor Tajur 1 in providing financing for KUR funds during the Covid 19 pandemic to financing customers for MSME actors, and how the impact of People's Business Credit (KUR) funds on Micro Business actors. This research method is a type of qualitative research with a field research method approach (field research) which is the object of this research, na mely 4 KUR financing customers and 2 staff employees of Bank Syariah Indonesia KCP Bogor Tajur 1. The results of the research at Bank Syariah Indonesia KCP Bogor Tajur 1 played a role in MSME customers during the Pandemic, namely the existence of policies from the bank towards financing customers affected by the Covid - 19 pandemic who experienced congestion in payments, namely the addition of an installment period (restructuring), and the existence of increase in income and business development of financing customers after using KUR.